If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7 + -1x) = x (7 * 4 + -1x * 4) = x (28 + -4x) = x Solving 28 + -4x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 28 + -4x + -1x = x + -1x Combine like terms: -4x + -1x = -5x 28 + -5x = x + -1x Combine like terms: x + -1x = 0 28 + -5x = 0 Add '-28' to each side of the equation. 28 + -28 + -5x = 0 + -28 Combine like terms: 28 + -28 = 0 0 + -5x = 0 + -28 -5x = 0 + -28 Combine like terms: 0 + -28 = -28 -5x = -28 Divide each side by '-5'. x = 5.6 Simplifying x = 5.6
| x(5x+3)=2x^2-8x+4 | | A-15=31 | | (102/5+8)+51/5 | | f(3)=2x+5 | | 2[x+5]=18 | | -6(y-t)=12t | | 6E-12=36 | | -5-(-4)+21= | | (-8)(-4)(-1)(-1)= | | 2[x+15]=18 | | 444=8T-4 | | 7*3*x=105 | | Xx0.4=15 | | 7x^3+182x^2-189x=0 | | 7x^3+182x^2-189x | | 2x/5=6/40 | | 12-20/4(-16)+23= | | 1/5(2x-7)=3 | | 11x+11=44 | | -4--3= | | -2x=-47 | | 3-y-2=y | | 2x+27=3+6x | | (2m-8n)(8m+8n)= | | 5x/6=20 | | 123+4= | | 5x+54=3x+76 | | 9x+17=53 | | (7+5i)(4-8i)=0 | | 4x^2+12xy-32y= | | (3)(-1)(-5)(-4)(2)= | | 15a-3a=3-7a |